Reference Values and Prediction Equation for Six-Minute Walk Distance in Children Aged 6-12 Years (African Journal of Biomedical Research, 2022)
The Six-Minute Walk Test (6MWT) is a self-paced, inexpensive sub-maximal exercise test used as a reliable and valid measure of exercise capacity in children and adolescents. The American Thoracic Society has recommended establishment of specific reference values for Six-Minute Walk Distance (6MWD) for each population in various age groupings and ethnicities. However, limited information exists on reference values for different age groups in Nigeria. This study was designed to generate reference values for apparently healthy Nigerian children, aged 6-12 years. This cross-sectional study involving 334 apparently healthy Nigerian children was approved by the appropriate Health Research Ethics Committee. Their physical and selected physiological characteristics were measured and determined, as appropriate. Each participant had a single trial of the 6MWT and distance covered was recorded. Data were analysed using both descriptive and inferential statistics at p